Secret. - Hughes, Kathryn ([Place of publication not identified] : Headline Review, 2016)
Mary has been nursing a secret. Forty years ago, she made a choice that would change her world for ever, and alter the path of someone she holds dear. Beth is searching for answers. She has never known the truth about her parentage, but finding out could be the lifeline her sick child so desperately needs. When Beth finds a faded newspaper cutting amongst her mother's things, she realises the key to her son's future lies in her own past. She must go back to where it all began to unlock...The Secret.
Keywords: 1900-1999; Mother and child -- Fiction; Family secrets -- Fiction; Kidneys -- Transplantation -- Patients -- Fiction; Family secrets; Kidneys -- Transplantation -- Patients; Manners and customs; Mother and child; England -- Social life and customs -- 20th century -- Fiction; England; Domestic fiction; Domestic fiction; Fiction